Socio-cultural Impact of Stunting Phenomenon on Children's Health in Medan City - Lumbanraja, Victor; Nasution, Nabila Fahira; Magello, Andi Nisa (Talenta Publisher, 2024)
Stunting is a health disorder that affects the growth and development of children caused by chronic nutrition and impacts cognitive and motor development. Other factors, such as the social and economic environment, can cause stunting. Medan City also has many stunting cases, which is caused by a lack of public understanding of the phenomenon. This research used a descriptive qualitative research method with a literature review approach. Data collection techniques through secondary data in the form of previous research, online media, and journals. Data analysis techniques using data reduction, data display, and conclusion drawing. The results of the study show that the efforts made by the Medan City government, such as nutritional interventions to conduct socialization in the community, still need to be improved. This is due to cultural perceptions that stunting is not a severe disease but is caused by several factors, such as genetics, misconceptions, and religion.